3x-2(5x-2)=-17

Simple and best practice solution for 3x-2(5x-2)=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2(5x-2)=-17 equation:


Simplifying
3x + -2(5x + -2) = -17

Reorder the terms:
3x + -2(-2 + 5x) = -17
3x + (-2 * -2 + 5x * -2) = -17
3x + (4 + -10x) = -17

Reorder the terms:
4 + 3x + -10x = -17

Combine like terms: 3x + -10x = -7x
4 + -7x = -17

Solving
4 + -7x = -17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -7x = -17 + -4

Combine like terms: 4 + -4 = 0
0 + -7x = -17 + -4
-7x = -17 + -4

Combine like terms: -17 + -4 = -21
-7x = -21

Divide each side by '-7'.
x = 3

Simplifying
x = 3

See similar equations:

| -4x^2-5x+84=0 | | 6(2f+8)=24 | | 3x-3=6x-2 | | 4/5(x-10)=4(8-x) | | ln(4x+11)=2 | | (-3m)-5=2m-15 | | -5a^2-10a+40=0 | | 14x-5x=12 | | 6x-11=-73-6x | | 3x+2y=2.50 | | 4(2d-5)=12 | | 2n+7n-10=2n-3n+10 | | -2q=88-5q | | x/180=70 | | 12+2n= | | -2k^2-7k+19=0 | | y=9+9 | | y=1+9 | | 2.5*3.5*h=35 | | 12y^3+13y^2+3y=0 | | (3m-3)/6=12 | | 7x^2y^2-3xy+4x^2y^2-8xy= | | -6(-12x-10)= | | 48=x^2-4 | | 2.3+6.9= | | 6(-12x+10)= | | -3n^2-5n+8=0 | | -12(-6x+5)= | | 2x+5y=2.95 | | x-15=2x-3 | | 5(x+2)-3=3x+15 | | -26+3=-39+14x |

Equations solver categories